2018
DOI: 10.1136/jramc-2018-000928
|View full text |Cite
|
Sign up to set email alerts
|

UK military doctors; stigma, mental health and help-seeking: a comparative cohort study

Abstract: IntroductionStudies suggest that medical doctors can suffer from substantial levels of mental ill-health. Little is known about military doctors’ mental health and well-being; we therefore assessed attitudes to mental health, self-stigma, psychological distress and help-seeking among UK Armed Forces doctors.MethodsSix hundred and seventy-eight military doctors (response rate 59%) completed an anonymous online survey. Comparisons were made with serving and ex-military personnel (n=1448, response rate 84.5%) par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
(21 reference statements)
0
18
1
Order By: Relevance
“…It cannot be said with conviction if this frequency is higher than that before the pandemic but a study performed in 2003 among surgeons 12 showed an increase in prevalence of depression after the severe acute respiratory syndrome outbreak, with a 30% increase in suicide. Poor mental health is a social stigma 13 ; moreover, a fear of being judged may explain why neurosurgeons have a lower depression score, as found in another study assessing level of stress among surgeons. 11 This may be one of the reasons that despite mental health problems and psychosocial issues among health care workers, most do not often seek mental health care.…”
Section: Discussionmentioning
confidence: 90%
“…It cannot be said with conviction if this frequency is higher than that before the pandemic but a study performed in 2003 among surgeons 12 showed an increase in prevalence of depression after the severe acute respiratory syndrome outbreak, with a 30% increase in suicide. Poor mental health is a social stigma 13 ; moreover, a fear of being judged may explain why neurosurgeons have a lower depression score, as found in another study assessing level of stress among surgeons. 11 This may be one of the reasons that despite mental health problems and psychosocial issues among health care workers, most do not often seek mental health care.…”
Section: Discussionmentioning
confidence: 90%
“…Studies have identified that there are many differing barriers to mental health treatment in military populations, including stigma 5–7. As discussed by Sharp et al ,8 many of us feel that if we acknowledge a perceived weakness, there would be concerns about our leadership and competency, and being seen as weak or as malingering.…”
mentioning
confidence: 99%
“…Common symptoms of burnout include treating patients and colleagues as objects rather than human beings, feeling emotionally depleted, physical exhaustion, poor judgement, cynicism, guilt, feelings of ineffectiveness and a sense of depersonalisation in relationships with coworkers or patients 12. The detrimental effects of stress in an emergency department or in a Regimental Aid Post12 and those events seen on deployment5–7 are well documented and have included doctors reporting suicidal thoughts 4. The perspective detailed in box 3 provides a reflection following a colleague’ s death in emergency medicine.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recognition of this I have made the Editor’s choice for this issue their study looking at stigma, mental health and help-seeking in UK military doctors 12. I have also seen considerable interest from authors submitting to JRAMC on resuscitative endovascular balloon occlusion of the aorta, and we have three papers and two letters to the editor on the subject between this issue and forthcoming issues on the subject 4.…”
mentioning
confidence: 99%